Health risks from hazardous waste disposal: the need for international scientific cooperation - Marsili, Daniela; Fazzo, Lucia; Comba, Pietro (European Journal of Oncology and Environmental Health, 2009)
Adverse health effects due to waste management practices, and in particular of hazardous waste, potentially represent a public health issue in many less-developed regions and developing countries, because of growing waste production, inadequate waste management practices, lack of appropriate legislation and control systems, as well as of growing illegal hazardous waste transboundary movements driven by the most industrialized countries. According to the Report of the WHO Workshop held in Rome in 2007 “….the scientific literature on the health effects of landfills provides some indication of the association between residing near a landfill site and adverse health effects. The evidence, somewhat stronger for reproductive outcomes than for cancer, is not sufficient to establish the causality of the association. However a public health response is warranted”. Moreover, there is evidence and the global awareness of growing transboundary movements of hazardous waste from the most industrialized countries to less developed regions and developing countries. Export and import of hazardous wastes, as well as their regional final destination within a country, are driven by economic, political, environmental and technological factors such as differences in prices for treatments and disposal, different taxation levels for wastes, insufficient waste treatment capacity and technology, among several others. In this paper we aim to emphasize the need for developing international scientific cooperation activities in this field in the near future with the perspective to create an appropriate framework to promote studies, transfer of knowledge and technology as well as to widespread awareness on health risks from hazardous waste disposals.